Transfer of fatty acids across the swine uterus and placenta - Thulin, A.J.; Allee, G.L.; Harmon, D.L.; Schoneweis, D.A.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The transfer across the swine uterus and placenta of [1-14C] octanoic acid, [9,10(n)- H] palmitic acid, and [1- 14C] linoleic acid was studied in five gilts and their fetuses during late gestation, following a single bolus injection. Only trace amounts of labeled fatty acids were found in fetal plasma lipid. There were no measureable differences in free fatty acids (FFA) from umbilical artery, and veinous blood. Concentration of FFA in fetal blood was about 40% of the level of uterine values (187, 194, 73, and 82 µEg/1 for uterine artery, uterine vein, umbilical artery, and umbilical vein). In addition, fetal plasma contained larger amounts of 14:0, 16:1, 18:1, and 20:4, whereas maternal plasma contained larger amounts of 18:0 and 18:2. These results indicate that only trace amounts of FFA cross the swine utero-placental unit during late gestation, which are probably not enough to increase energy supply or lipid storage of the fetus.
Keywords: Swine; Fatty acids; Swine uterus; Placenta